Analysis of MSMEs’ Taxpayer Compliance: Impact of E-Filling Implementation, Tax Incentive Policy, and Quality of Tax Service - Muhammad Hadiwijaya; Deden Tarmidi (IAEI, 2023)
This study aims to analyze the influence of E-Filing Implementation, Tax Incentive Policies and Quality of Fiscal Services on MSME Taxpayer Compliance. The population in this study are SMEs (Micro, Small and Medium Enterprises) who are domiciled and run their businesses in the Keroncong sub-district, Jatiuwung sub-district, Tangerang City. With Non-Probability Sampling Technique, the sample used in this study was 100 MSME respondents. Using a questionnaire in the collection data and uses a Likert scale, this study also uses causal research to test the hypothesis. Smart 4 software used in the descriptive analysis and all of statistic test to hypothesis analysis, with outer model and inner model analysis. The results of the study show that the implementation of E-Filing and quality of tax services have the significant effect on taxpayer compliance, while Tax Incentive Policies have no significant effect on taxpayer compliance. These results can be input for the directorate general of taxes in increasing MSME tax compliance by improving tax services and also e-Filling operations.